Dams engineering in a social and environmental context : proceedings of the 17th Conference of the British Dam Society at the University of Leeds from 12 - 15 September 2012 - Pepper, Andrew (ICE Pub., 2012)
This book contains the proceedings of the 17th Biennial Conference of the British Dam Society, Dams: Engineering in a Social and Environmental Context. It covers practical aspects which are directly relevant to all who work in the design, construction or management of dams and reservoirs, both in the UK and abroad.